Bilingualism and multilingualism in the Roman world - Mullen, Alex (Oxford University Press, 2015)
Roman authors referred to Latin and Greek as utraque lingua (both our languages), and the study of Classics has traditionally entailed an appreciation of the entanglement and complex relations between Latin and Greek language and literature. However, the Roman world was linguistically diverse—multilingual, not bilingual. Especially since the pioneering work of James Adams (Adams 2003, cited under General Overviews), classicists have begun to engage more fully with modern bi- and multilingualism theory and practice and to explore more systematically beyond Latin and Greek, literature, and the elite. This article is designed to introduce some of the key scholarship in this rapidly expanding and important field, presenting not only recent works, but also some of the earlier research that remains influential. It begins with a selection of general overviews, which characterize the new wave and more traditional approaches. It then offers a short selection of general surveys of languages in the Roman world and introductory, influential texts in modern bilingualism studies. The rest of the article is split loosely between epigraphic regional studies, literary bilingualism, and technical linguistic studies. Discussion in the Regional Studies section makes it clear that some areas (e.g., Egypt) have a long tradition of investigation into bi- and multilingualism, whereas others remain relatively under-researched. In the largely literary sections, the focus is on Greek and Other Languages in Latin Literature, Translation Literature, and “Roman Greek”, which concentrates on the Greek of Roman writers and also considers epigraphic sources such as the senatus consulta. In these sections the viewpoint is primarily on bi- and multilingualism in literary and related sources and does not seek to encompass the wider literary scholarship. The final section, Technical Linguistic Studies, contains research related to both lexical and non-lexical contact phenomena.